Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Jigsaw Di Kelas IV Sekolah Dasar - Febriani, Silki; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This research is motivated by the lack of teachers providing opportunities for students to solve problems that make students not too understand what they are learning. This tudy aims to describe the results of integrated thematic learning using a model of cooperative learning type jigsaw,  class of elementary school 10 Bandar Buat, Padang. This type of research is classroom action research with qualitative and quantitative appoarches. This research was conducted in the second semester of the 2018/2019 academic year. This research was conducted in 2 cycles.  The result of the study of students learning, there is a change in the aspect of knowledge in the first cycle which achieved an average score of 61,75% in sulfficient category (C) increased to 91% in the excellent category (SB) in cycle II. Keywords: